Returns to citizenship?: Evidence from Germany's recent immigration reforms - Gathmann, Christina; Keller, Nicolas (CESifo working papers, 2014)
Immigrants in many countries have lower employment rates and lower earnings than natives. We study whether a more liberal access to citizenship improves the economic integration of immigrants. Our analysis relies on two major immigration reforms in Germany, a country with a weak record of immigrant assimilation. For identification, we exploit discontinuities in the reforms'eligibility rules. We find few returns of citizenship for men, but substantial returns for women. Returns are also larger for poorer and more recent immigrants, but essentially zero for traditional guest workers. Overall, liberalization of citizenship provides some economic benefits but is unlikely to result in full integration of immigrants in the host country.